2019
DOI: 10.2147/cmar.s217872
|View full text |Cite
|
Sign up to set email alerts
|

<p>Skin lesions in chronic myeloid leukemia patients during dasatinib treatment</p>

Abstract: PurposeIn our work we sought to define the prevalence rates of cutaneous events during dasatinib therapy in chronic myeloid leukemia (CML) patients and to investigate the clinical and pathological characteristics of these reactions.Patients and methodsIn our institution, 67 CML patients were treated with dasatinib. it was given as first line treatment in 26 (39%) and subsequent treatment in 41 (61%) CML patients. Flow cytometry analysis of peripheral blood and cutaneous biopsy was done on all CML patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
1
6
0
2
Order By: Relevance
“…With treatment of LC, nonleukemic cutaneous manifestations can be seen including purpura, leukocytoclastic vasculitis, neutrophilic dermatoses (such as Sweet syndrome and pyoderma gangrenosum), panniculitis, and infection. Many of these cutaneous manifestations are well‐known adverse reactions to tyrosine kinase inhibitors (TKIs), which are the first‐line treatment in CML as they target the BCR‐ABL1 oncoprotein 3,4,11 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With treatment of LC, nonleukemic cutaneous manifestations can be seen including purpura, leukocytoclastic vasculitis, neutrophilic dermatoses (such as Sweet syndrome and pyoderma gangrenosum), panniculitis, and infection. Many of these cutaneous manifestations are well‐known adverse reactions to tyrosine kinase inhibitors (TKIs), which are the first‐line treatment in CML as they target the BCR‐ABL1 oncoprotein 3,4,11 …”
Section: Discussionmentioning
confidence: 99%
“…Many of these cutaneous manifestations are well-known adverse reactions to tyrosine kinase inhibitors (TKIs), which are the first-line treatment in CML as they target the BCR-ABL1 oncoprotein. 3,4,11 The diagnosis of LC is predominantly based on the histopathology and the immunophenotype of the leukemic infiltrate in correlation with the patient's prior history of leukemia if known. Histopathologically, LC typically spares the epidermis and involves the dermis and/or subcutis in a diffuse or nodular pattern and often with perivascular and/or periadnexal involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some protein kinase inhibitors used as cancer chemotherapeutics, such as Alectinib, Cyc-116, Dasatinib, and Vemurafenib, are known to elicit photosensitivity as one of their side effects ( Chapman et al, 2011 ; Peters et al, 2017 ; Tarantini et al, 2019 ). Further characterization of these drugs revealed that most of them bind to and inhibit ferrochelatase ( Klaeger et al, 2016 ).…”
Section: Regulation Of Ferrochelatase Activitymentioning
confidence: 99%
“…Se han descrito también reacciones como queratosis pilaris o similares, reacciones liquenoides (47,48) , liquen mucoso erosivo (49) , lipoma de células fusiformes, foliculitis en penacho, paniculitis granulomatosa (50) , pseudoporfiria, xerosis cutánea, alopecia, urticaria, eritema multiforme, vasculitis, úlcera cutánea, fibrosis, pustulosis exantemática, dermatosis neutrofílica, paniculitis y síndrome de Stevens-Johnson (51) . En la Tabla 3 se recopilan algunas características histopatológicas reportadas de los efectos adversos cutáneos en pacientes en manejo con ITC.…”
Section: Otros Efectos Adversos Dermatológicos De Los Inhibidores De ...unclassified